Rendimiento de la Producción del Maíz en la Finca Keily - Montero Aspiazu, Kelly Silvana (2017)
The National Information System (SINAGAP) of the Ministry of Agriculture, Livestock, Aquaculture and Fisheries (Magap), indicates that the national yield of the hard corn crop for the winter season of 2016 was 5.53 (t / ha), the which was 2% higher than the similar season of 2015. During that period maize production had a performance in different yields in different areas. For example, in Loja and Manabí provinces 21% and 25%, respectively, while in Guayas and Los Rios decreased by 9% and 13%, respectively, due to phytosanitary problems. In winter 2016 a national production of 1'064,380 metric tons of cereal was estimated, a 20% reduction compared to 2015. The study reveals that 71% of the producers surveyed stated that they were affected by phytosanitary problems . While 29% for other problems, lack of water, quality of inputs, quality of seeds; (The Telegraph, 2017). The present work shows the research carried out at the Keily Farm, which performs two types of production: Maize production and the production of timber trees. The objective of this project is the revision of the items of income and expenses that the farm has to generate corn production and to know if this production generates profitability when compared to the industry. This project has focused directly on the production of maize specifically to the controls of its income and expenses, to know its performance, since this farm must know what are its items of expenditure and what are its revenue items